Global urban expansion offsets climate-driven increases in terrestrial net primary productivity - Xiaoping Liu (Nature Portfolio, 2019)
Robust estimates of either urban expansion worldwide or the effects of such phenomenon on terrestrial net primary productivity (NPP) are lacking. Here the authors used the new dataset of global land use to show that the global urban areas expanded largely between 2000 and 2010, which in turn reduced terrestrial NPP globally.